Periodontitis among a Group of Type TwoDiabetic Patientsin Relation to Risk of Vascular Disease - Abbas, Dalia K; El-Samarrai, Sulafa K (Journal of Baghdad College of Dentistry, 2016)
Background: Type two diabetic patients have higher risk of cardiovascular and periodontal disease. Furthermore, patients with more severe periodontal disease have higher incidence of cardiovascular disease. This study aimed to assess the association between periodontal health status and the risk of vascular disease in type 2 diabetic patients. Materials and Methods: One hundred type 2 diabetes mellitus patients and fifty apparently healthy males were enrolled in this study. Oral examinations conducted were; plaque Index, calculus index, gingival index, probing pocket depth, and clinical attachment level. For the assessment of vascular risk, arterial stiffness index was used. Results: According to arterial stiffness index, type 2 diabetic patients were categorized into two groups: Group A: type 2 diabetic patients without vascular disease risk. Group B: type 2 diabetic patients with vascular disease risk. The periodontal disease parameters including gingival index, probing pocket depth, and clinical attachment level were higher in healthy controls in comparison to diabetics and in group B in comparison to group A. The difference between group A vs. group B for probing pocket depth is of highly significant (P